Program Aplikasi Penerimaan dan Pengeluaran Kas Berbasis Web pada PT.Pelindo Daya Sejahtera Banjarmasin - Nadia Puteri Utami; Heru Kartika Chandra; Azra Nur Izzati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to find out whether the accounting information system for cash receipts and disbursements is running effectively and efficiently. Meanwhile, the benefit of this research is as material for consideration and input in improving cash receipt and disbursement procedures at PT. Pelindo Daya Sejahtera, and to produce a Web-Based Cash Receipts and Disbursements Application Program. In this research the author used primary data and secondary data such as interview results, observations and documentation.The theoretical framework is to analyze the Cash Receipts and Disbursements Accounting Information System, namely by analyzing the information needed by management, related functions, procedural networks, documents and accounting records used, as well as document flowcharts.From this research it was found that all cash recording at PT Pelindo Daya Sejahtera is still semi-manual, namely using Microsoft Excel. The author suggests that PT Pelindo Daya Sejahtera use the Web-Based Cash Receipts and Disbursements Application Program to help record cash receipts and disbursements data, as well as make it easier to create reports effectively and efficiently.